Congenital deficiency of factor XIII - Özsoylu, Şinasi; Yamak, Behice (The Turkish Journal of Pediatrics, 1969)
A four-month-old male infant with congenital deficiency of the fibrin stabilizing factor is described. He presented prolonged umbilical bleeding, and subdural and cerebromeningeal hemorrhage, all of which were controlled by whole blood transfusions. The coagulation studies in this case were within normal limits, except for the solubility of the clot in one per cent monochloracetic acid. By mixture studies the heterozygosity of both parents was also shown.